Rheology study of water-in-crude oil emulsions - Wong, Siew Fan; Law, Ming Chiat; Samyudia, Yudi; Dol, Sharul Sham (2015)
An emulsion is a mixture of two immiscible liquids, whereby droplets of one phase (dispersed phase) are encapsulated in another phase (continuous phase). Emulsions formation in pipelines is one of the most critical problems faced by the oil and gas industries. To solve this unfavourable emulsification problem, the rheological properties of emulsions have to be determined first because they have different effects on the transportation of fluid. In this paper, the rheological properties of water-in-crude oil (W/O) emulsions will be presented for discussion or reference. Bintulu light crude oil was used as the continuous phase and water was used as the dispersed phase to form the W/O emulsions. The experimental results have demonstrated that W/O emulsions with volume fraction of water greater than or equal to 0.1 displays a Newtonian fluid property for shear rates below 500 s-1. For shear rates above 500 s-1, they display a non-Newtonian fluid property. Different volumes of water phase result in different viscosities as well. The viscosity of W/O emulsion increases with the volume of water from 10 % up to 35 %. Then, it decreases with further increase in the volumes of water up to 100 %. For 10 % to 35 % of water volumes, increasing in viscosity is due to the increase in the amount of dispersed phase droplets which leads to higher friction among droplets. Meanwhile, for 40 % to 100 % of water volumes, the droplets start to coalesce and form larger droplets causing a specific area to decrease. Hence, the friction among the droplets is reduced. This leads to a decrease in viscosity. In general, the W/O emulsions for the volume fractions of water which are less than 0.8 will behave as a Newtonian fluid in turbulent flow.